Expression of ICAM-1, HLA-DR, and CD80 on peripheral circulating CD1 α DCs induced in vivo by IFN-α in patients with chronic hepatitis B - Yu, Yong-Sheng (Baishideng Publishing Group Co., Limited, 2006)
AIM: To explore the effects of interferon-α (IFN-α) application on peripheral circulating CD1α dendritic cells (DCs) in patients with chronic hepatitis B, and the expression of HLA-DR, CD80, and ICAM-1 on CD1α DCs in order to explore the mechanism of immune modulation of IFN-α. METHODS: By flow cytometry technique, changes of CD1α DCs were monitored in 22 patients with chronic hepatitis B treated with IFN-α and in 16 such patients not treated with IFN-α within three months. Meanwhile, the expression of HLA-DR, CD80, and ICAM-1 on CD1α DCs was detected. RESULTS: In the group of IFN-α treatment, the percentage of CD1α DCs in peripheral blood mononuclear cells was increased after three months of therapy. In patients who became negative for HBV-DNA after IFN-α treatment, the increase of DCs was more prominent, while in control, these changes were not observed. Increased expression of HLA-DR, CD80, and ICAM-1 on CD1α DCs was also observed. CONCLUSION: CD1α DCs can be induced by IFN-α in vivo, and the immune related molecules such as HLA-DR, CD80, and ICAM-1 are up-regulated to some degree. This might be an important immune related mechanism of IFN-α treatment for chronic hepatitis B.